Library automation networking in dental college library in Rajasthan: a case study - Mathur, Anamika (Universal Research Reports, 2018)
The library and information centre is an important component of any educational institution, which is hub of the teaching, and learning activities where students, researchers and teachers can explore the vast resources of information. In the traditional libraries users have to send more time for searching a small piece of information and for that have to depend mainly on the library professional or library staff. But in the age of information communication technology, computers are being used for day-to-day housekeeping activity of the library which saves the time of the end users, and library professional also and at the same time avoid duplication of work and make the library service smooth and effective. Resource sharing library networks have been functioning effectively in developed countries since 1930s. In India, computerization and networking activities started with the establishment of National information System for Science and Technology (NISSAT) in 1979. In the beginning, the major constraints of library automation were absence of planning, non-availability of vendor developed software at affordable prices, restrictions on the import of hardware, lack of trained manpower, non-existence of standards, and absence of co-operation.